2021
DOI: 10.1155/2021/5034269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the WeChat Platform Health Management and Refined Continuous Nursing Model on Life Quality of Patients with Acute Myocardial Infarction after PCI

Abstract: The purpose was to explore the effect of the WeChat platform health management and refined continuous nursing model on life quality of patients with acute myocardial infarction (AMI) after PCI. 100 AMI patients treated in the cardiovascular medicine of the First Affiliated Hospital of Soochow University from June 2018 to June 2019 were selected as the study subjects and randomly divided into research group and reference group, with 50 cases in each group. The reference group received routine nursing after PCI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
13
0
3
Order By: Relevance
“… 9 Xu et al similarly studied the impact of the WeChat video- messaging platform on 100 patients post PCI randomised to either conventional care or digital support comprising daily health advice and two-weekly video lectures. 25 Although Xu et al found significant improvements in medication compliance in those receiving telemedical interventions (t=5.482, p<0.001), as well as greater nursing satisfaction (p<0.001) and reduced emotional volatility (P<0.001), data from Bikmoradi et al at 4-weeks post discharge demonstrated a lack of significant differences between control groups and telenursing groups in adherence to medication. 9 …”
Section: Resultsmentioning
confidence: 94%
“… 9 Xu et al similarly studied the impact of the WeChat video- messaging platform on 100 patients post PCI randomised to either conventional care or digital support comprising daily health advice and two-weekly video lectures. 25 Although Xu et al found significant improvements in medication compliance in those receiving telemedical interventions (t=5.482, p<0.001), as well as greater nursing satisfaction (p<0.001) and reduced emotional volatility (P<0.001), data from Bikmoradi et al at 4-weeks post discharge demonstrated a lack of significant differences between control groups and telenursing groups in adherence to medication. 9 …”
Section: Resultsmentioning
confidence: 94%
“…At present, it has developed into the most common cause of end-stage renal disease in middle-aged and elderly people. 17 It has the characteristics of long course of disease and repeated condition. At present, there is no specific drug for the treatment of this disease in clinical practice, and most patients need long-term or lifelong medication for treatment, so patients need to have high autonomy and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Numerous clinical studies have confirmed that the patients after PCI can benefit greatly from lifestyle changes, rational rehabilitation training and risk reduction behaviors. [36][37][38][39] Nurses can play a key role in education and care, supporting and facilitating patient participation in these risk reduction activities. [40] Empowerment education is an innovation and upgrade of the previous conventional nursing education.…”
Section: Discussionmentioning
confidence: 99%